Geographical Indications in Bangladesh Supply Chain: What Needs to Be Done Now? - Sabiha Matin; Shahid Hussain Shamim (International Journal of Supply Chain Management, 2018)
Each country has its own standards to live up to. Geographical Indications is a type of Intellectual Property that recognize products to bear a certain reputation for themselves based on the country of its origin. It is logical to assume that they contain characteristics, like their quality, that are dependent on factors such as environmental or human characteristics. The role of Geographical Indications is vital in Intellectual Property and is gaining recognition rightfully. Bangladesh supply chain also enacted this act recently and is in the process of registering its traditional and specialized products. The present paper takes a synopsis of the existing scenario of Geographical Indications in Bangladesh supply chain. The paper will also show some strategies and roadmap from marketing perspectives to be taken by the authorities to reach and meeting the needs of the target customers of this particular sector. Two research methods, Case Study and In-depth Interviews have been used to collect primary data. A necessary aspect of this paper is how it sheds light on aspects that are needed to benefit from stimulating areas of GI and its proper application. Another vital discussion is regarding the increase in activities required to improve the marketing scheme of GI application. Enhancing quality is key to improving the products and the market. To secure the position of GI and their beneficiaries in Bangladesh supply chain, it is necessary that the Ministry if Industries works in collaboration and harmony with them.